Durability of the neutralizing antibody response to vaccine and non-vaccine HPV types 7 years following immunization with either Cervarix® or Gardasil® vaccine. Issue 18 (24th April 2019) - Godi, Anna; Panwar, Kavita; Haque, Mahmoud; Cocuzza, Clementina E.; Andrews, Nick; Southern, Jo; Turner, Paul; Miller, Elizabeth; Beddows, Simon
Abstract: Bivalent (Cervarix®) and quadrivalent (Gardasil®) Human Papillomavirus (HPV) vaccines demonstrate remarkable efficacy against the targeted genotypes, HPV16 and HPV18, but also a degree of cross-protection against non-vaccine incorporated genotypes, HPV31 and HPV45. These outcomes seem to be supported by observations that the HPV vaccines induce high titer neutralizing antibodies against vaccine types and lower responses against non-vaccine types. Few data are available on the robustness of the immune response against non-vaccine types. We examined the durability of vaccine and non-vaccine antibody responses in a follow up of a head-to-head study of 12–15 year old girls initially randomized to receive three doses of Cervarix® or Gardasil® vaccine. Neutralizing antibodies against both vaccine and non-vaccine types remained detectable up to 7 years following initial vaccination and a mixed effects model was used to predict the decline in antibody titers over a 15 year period. The decline in vaccine and non-vaccine type neutralizing antibody titers over the study period was estimated to be 30% every 5–7 years, with Cervarix® antibody titers expected to remain 3–4 fold higher than Gardasil® antibody titers over the long term. The antibody decline rates in those with an initial response to non-vaccine types were similar to that of vaccine types and are predicted to remain detectable for many years. Empirical data on the breadth, magnitude, specificity and durability of the immune response elicited by the HPV vaccines contribute to improving the evidence base supporting this important public health intervention. Original trial:ClinicalTrials.gov NCT00956553.